Comparing the Psychological Effects of Meditation- and Breathing-Focused Yoga Practice in Undergraduate Students - Qi, Xin; Tong, Jiajin; Chen, Senlin; He, Zhonghui; Zhu, Xiangyi (Frontiers in Psychology, 2020)
Objectives: The present study aimed to compare the psychological effects of meditation- and breathing-focused yoga practice in undergraduate students. Methods: A 12-week yoga intervention was conducted among a group of undergraduate students enrolled in four yoga classes at an academically prestigious university in Beijing, China. Four classes were randomized to meditation-focused yoga or breathing-focused yoga. A total of 86 participants finished surveys before and after the 12-week intervention, measuring work intention, mindfulness, and perceived stress. The repeated-measure multivariate analysis of covariance (MANCOVA) followed by univariate analyses were conducted to examine the differences in work intention, mindfulness, and stress between the two yoga intervention groups over the semester, after controlling for age and gender. Results: The repeated-measure MANCOVA revealed significant group differences with a median effect size (Wilks’ lambda, Λ= .90, F (3,80) = 3.10, p = .031, η2 = .104). Subsequent univariate analyses showed that students in the breathing-focused yoga group had significant higher work intentions (F1,82 = 5.22; p = .025; η_p^2= .060) and mindfulness (F1,82 = 6.33; p = .014; η_p^2= .072) but marginally lower stress (F1,82 = 4.20; p = .044; η_p^2= .049) than students in the meditation-focused yoga group. Conclusion: Yoga practice with a focus on breathing is more effective than that with a focus on meditation for undergraduates to retain energy for work, keep attention and awareness, and reduce stress.